Pregnancy does not modify the risk of MS in genetically susceptible women. Issue 6 (November 2020) - Adams, Cameron J.; Wu, Sean L.; Shao, Xiaorong; Bradshaw, Patrick T.; Gonzales, Edlin; Smith, Jessica B.; Xiang, Anny H.; Bellesis, Kalliope H.; Chinn, Terrence; Bos, Steffan D.; Wendel-Haga, Marte; Olsson, Tomas; et al.
Abstract : Objective: To use the case-only gene-environment (G E) interaction study design to estimate interaction between pregnancy before onset of MS symptoms and established genetic risk factors for MS among White adult females. Methods: We studied 2, 497 female MS cases from 4 cohorts in the United States, Sweden, and Norway with clinical, reproductive, and genetic data. Pregnancy exposure was defined in 2 ways: (1) live birth pregnancy before onset of MS symptoms and (2) parity before onset of MS symptoms. We estimated interaction between pregnancy exposure and established genetic risk variants, including a weighted genetic risk score and both HLA and non-HLA variants, using logistic regression and proportional odds regression within each cohort. Within-cohort associations were combined using inverse variance meta-analyses with random effects. The case-only G × E independence assumption was tested in 7, 067 individuals without MS. Results: Evidence for interaction between pregnancy exposure and established genetic risk variants, including the strongly associated HLA-DRB1*15:01 allele and a weighted genetic risk score, was not observed. Results from sensitivity analyses were consistent with observed results. Conclusion: Our findings indicate that pregnancy before symptom onset does not modify the risk of MS in genetically susceptible White females.